Advances in stationary and portable fuel cell applications. (5th October 2016) - Wilberforce, Tabbi; Alaswad, A.; Palumbo, A.; Dassisti, M.; Olabi, A.G.
Abstract: The reliance on fossil fuels is one of the most challenging problems that need to be dealt with vigorously in recent times. This is because using them is not sustainable and leads to serious environmental issues, such as: air pollution and global warming. This condition affects economic security and development. An alternative to fossil fuel is highly possible which will be more environmentally friendly, sustainable and efficient as well. Among all the different technologies associated with renewable energy, fuel cell technologies represent one of the most promising technological advancement to curb the situation. In this paper, an overview of the technology and its advantages and disadvantages compared with competitive technologies was revealed. The application of different fuel cell types in the stationary and portable sectors was covered. Furthermore, recent challenges and promising developments of current fuel cell technologies in different studied applications were reviewed. Some possible solutions to the challenges were named in this paper for both the portable and stationary fuel cell applications. The paper further seeks to expose the world to the current progress made in the fuel cell industry up to date and possible areas that needs intensified research and modifications to make the fuel cell industry more vibrant and buoyant. Highlights: Overview of the fuel cell technology is given. Recent challenges facing the fuel cell market in stationary and portable sectors were reviewed. Up-to-date promising developments of fuel cell technologies in the stationary and portable sectors were covered.